2022
DOI: 10.30564/jsbe.v5i3.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Digital and Financial Awareness of Household Womens on the Use of Fin-Tech in India: Observing the Relation with (Utaut) Model

Abstract: Era of COVID-19 resulted in contactless transactions and extensive use of technological applications. Similar was the case of Fin-Tech which has extensively been used by consumers all around the globe for making transactions and other financial and economic needs. Although there is a lack of research to reflect these forms of evidence from the developing as well as Indian sides of the globe. On the other side, some studies indicated the Unified Household Acceptance and Use of Technology (UTAUT) model as the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Agarwal (2020) suggested that efforts should be made to promote financial and digital literacy among the general public. Financial literacy is significantly associated with the UTAUT model (Yadav, Tripathi, & Tripathi, 2022). According to Weedige, Ouyang, Gao, and Liu (2019), financial literacy is accentuated by informed decisions, protected consumers, economic independence, and peace of mind.…”
Section: Takaful Literacymentioning
confidence: 99%
“…Agarwal (2020) suggested that efforts should be made to promote financial and digital literacy among the general public. Financial literacy is significantly associated with the UTAUT model (Yadav, Tripathi, & Tripathi, 2022). According to Weedige, Ouyang, Gao, and Liu (2019), financial literacy is accentuated by informed decisions, protected consumers, economic independence, and peace of mind.…”
Section: Takaful Literacymentioning
confidence: 99%
“…The existing organizational stance, its short-and long-term goals, and the cultural background may all be accessed using the theoretical frameworks TAM, TTF, and UTAUT [27,28]. It is strongly advised that companies thoroughly research these works before selecting the right technology, vendor, and change management process to avoid misfiring in the future [29,30]. Additionally, study results may affect behavior motivators and outside variables when analyzing executive-level intents and may serve as a basis for future analyses of the DT projects.…”
Section: Recommendationsmentioning
confidence: 99%
“…Temuan studi yang dilakukan oleh Yadav et al, (2022) menunjukkan pentingnya mengembangkan literasi keuangan seseorang. Menurut Chen & Volpe, (1998) literasi keuangan adalah pemahaman tentang pengetahuan dasar untuk keuangan pribadi, pemahaman tentang simpan pinjam, pemahaman tentang asuransi, dan pemahaman tentang penggunaan layanan keuangan, salah satunya adalah penggunaan pembayaran online.…”
Section: Doiunclassified